2007
DOI: 10.1194/jlr.m700146-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Proteinuria increases oxylipid concentrations in VLDL and HDL but not LDL particles in the rat

Abstract: We previously established that proteinuria alters the apolipoprotein content of lipoproteins. This study was conducted to establish whether proteinuria also alters the concentrations of oxidized lipids within lipoprotein density fractions. To this end, we induced passive Heymann nephritis in Sprague Dawley rats and measured an array of alkaline-stable oxylipids in VLDL, LDL, and HDL particles. Proteinuria increased the total oxylipid amounts in the HDL and VLDL fractions. More importantly, these levels were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 45 publications
0
37
0
Order By: Relevance
“…In the VLDL fractions used for HAEC treatments, the LA-derived oxidized lipids 13-HODE and 9-HODE were elevated .10-fold, whereas LA increased ?3-fold during the 30 min lipolysis process. In a recent study, Goodfriend et al (58) observed a remarkable increase in nonesterified oxylipids in plasma from subjects who received heparin, suggesting that human TGRLs contain these oxidized lipids in vivo, as observed in rats (51). Therefore, it appears that significant amounts of oxidized lipids are released during TGRL lipolysis, and may be involved in eliciting responses in exposed endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…In the VLDL fractions used for HAEC treatments, the LA-derived oxidized lipids 13-HODE and 9-HODE were elevated .10-fold, whereas LA increased ?3-fold during the 30 min lipolysis process. In a recent study, Goodfriend et al (58) observed a remarkable increase in nonesterified oxylipids in plasma from subjects who received heparin, suggesting that human TGRLs contain these oxidized lipids in vivo, as observed in rats (51). Therefore, it appears that significant amounts of oxidized lipids are released during TGRL lipolysis, and may be involved in eliciting responses in exposed endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…Kreil et al observed an increase in lipoprotein oxylipids after hemorrhagic shock in human patients [5]. Newman et al have shown that experimental nephrosis in rats markedly increased the oxylipid content of lipoproteins [6].…”
Section: Discussionmentioning
confidence: 99%
“…We, thus, hypothesize that an effect modifier could modify the relationship between cholesterol and mortality. In CKD, both hypoalbuminuria and proteinuria could separately contribute to impaired lipoprotein catabolism and increased oxidative stress (14,15). We also propose that the relationship between cholesterol and mortality differs by amount of proteinuria.…”
Section: Introductionmentioning
confidence: 99%